Answer:
sqrt(65) =x
Explanation:
To find x, we need to get the height of that triangle. We can find it from the other triangle with 3 and 5
Using Pythagorean theorem
a^2 + b^2 = c^2 where a and b are the legs and c is the hypotenuse
3^2 + b^2 = 5^2
9 + b^2 = 25
Subtract 9 from each side
9-9 +b^2 = 25-9
b^2 =16
Take the square root of each side
sqrt(b^2) = sqrt(16) We only take the positive since a length must be positive
b =4
Now we can use the Pythagorean theorem on the triangle with x
a^2 +b^2 =c^2
7^2 + 4^2 = x^2
49+16 = x^2
65 = x^2
Take the square root of each side
sqrt(65) = sqrt(x^2)
sqrt(65) =x